Concurrent endurance and strength training not to failure optimizes performance gains - Izquierdo-Gabarren, M.; Gonzalez de Txabarri Exposito, R.; Garcia-Pallares, J.; Sanchez-Medina, L.; de Villarreal, E. S. S.; Izquierdo, M. (Medicine & Science in Sports & Exercise, 2010)
Purpose: The purpose of this study was to examine the efficacy of 8 wk of resistance training to failure versus not to failure training regimens at both moderate and low volumes for increasing upper-body strength and power as well as cardiovascular parameters into a combined resistance and endurance periodized training scheme.